2017
DOI: 10.5194/acp-17-7721-2017
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced toxicity of aerosol in fog conditions in the Po Valley, Italy

Abstract: Abstract. While numerous studies have demonstrated the association between outdoor exposure to atmospheric particulate matter (PM) and adverse health effects, the actual chemical species responsible for PM toxicological properties remain a subject of investigation. We provide here reactive oxygen species (ROS) activity data for PM samples collected at a rural site in the Po Valley, Italy, during the fog season (i.e., November–March). We show that the intrinsic ROS activity of Po Valley PM, which is mainly comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 56 publications
8
25
0
1
Order By: Relevance
“…The central valley fog is a persistent low-cloud feature observed in late autumn-winter months (Baldocchi & Waller, 2014;Herckes et al, 2015). Similar observations are seen over the Po valley, a low-lying extensive basin south of the Alps, where winter fog and pollution haze is frequently observed across the basin (Decesari et al, 2017;Giulianelli et al, 2014), with fog holes evident over urban/industrial cities (e.g., Milan).…”
Section: Urban Heat Islands and Fog Holessupporting
confidence: 56%
See 1 more Smart Citation
“…The central valley fog is a persistent low-cloud feature observed in late autumn-winter months (Baldocchi & Waller, 2014;Herckes et al, 2015). Similar observations are seen over the Po valley, a low-lying extensive basin south of the Alps, where winter fog and pollution haze is frequently observed across the basin (Decesari et al, 2017;Giulianelli et al, 2014), with fog holes evident over urban/industrial cities (e.g., Milan).…”
Section: Urban Heat Islands and Fog Holessupporting
confidence: 56%
“…Owing to its rich hydrological resources and agriculture, the IGP is among the most densely populated regions with over 900 million inhabitants. The fog period coincides with the severe anthropogenic winter haze in south and east Asia as well as elevated winter time pollution levels in the Po valley and California's central valley, with significant degradation to air quality (Decesari et al, 2017;Herckes et al, 2015;Sun et al, 2006;Wang et al, 2016). Polluted fog is widely known to affect public health (Stone, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recent investigations of the toxicology of PM-in form of reactive oxygen species (ROS) present in the aerosol particleshave shown that ROS can be produced in fog droplets. Hence, the fog-processed PM can be more harmful to health (Decesari et al, 2017).…”
Section: 1029/2018ef000952mentioning
confidence: 99%
“…Health effects research has primarily focused on contaminants such as polycyclic aromatic hydrocarbons, persistent organic pollutants, heavy metals, and mercury, rather than the most abundant air pollutants. Further, there is evidence that fog processes PM contains more reactive oxygen species (Decesari et al, 2017) and is hence more toxic. There is also a clear bias toward air pollution information in larger Arctic cities.…”
Section: Air Quality Impactsmentioning
confidence: 99%
“…Bourcier et al [33] have provided experimental evidence of biomass burning as a source of atmospheric 137 Cs present in cloud water. Fog droplets capturing radio-nuclides could either prolong or shorten the residence time of the radioactive atmospheric pollutants, by preventing fast deposition or enhancing it by scavenging [34]. Thus, fogs can play an important role in spreading, keeping close to the surface, and in wet deposition of radioactive particles, with direct impacts on the human health and ecosystems.…”
Section: Fog Types By the Kind Of Particles: Radioactive And Chemicalmentioning
confidence: 99%